2002
DOI: 10.1007/bf02981977
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CD55- and/or CD59-Deficient Red Cell Populations in Patients With Plasma Cell Dyscrasias

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired clonal disorder characterized by a decrease or absence of glycosylphosphatidylinositol (GPI)-anchored molecules such as CD55 and CD59 from the surface of affected cells, resulting in intravascular hemolysis, cytopenia, and venous thrombosis. A PNH-like phenotype has been detected in various hematological disorders, mainly in aplastic anemia and myelodysplastic syndromes, but also in lymphoproliferative syndromes (LPSs). To the best of our knowledge, CD55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…However the potential progress to B-cell malignant disease was rarely reported. The John Meletis [6] study about the information on the PNH phenotype in plasma cell dyscrasias (PCDs) found the two of seven patients with confirmed Waldenström macroglobulinemia (WM) can simultaneously present CD55…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the potential progress to B-cell malignant disease was rarely reported. The John Meletis [6] study about the information on the PNH phenotype in plasma cell dyscrasias (PCDs) found the two of seven patients with confirmed Waldenström macroglobulinemia (WM) can simultaneously present CD55…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing literature, malignant transformation is mainly acute myeloid leukemia [4,5]. Terminating B cell lymphoma even more seldom seen in literature [6]. Here, we report a PNH case terminating with Waldenström macroglobulinemia (WM) and T cell monoclonal expansion and review the literature.…”
mentioning
confidence: 94%
“…Ten patients were found to have PNH and plasma cell dyscrasias, including 1 patient with PNH and MGUS and 4 patients with PNH and IgG multiple myeloma [11]. Monoclonal gammopathies can also occur in association with T cell clonal expansions [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…PNH has also been described with concurrent plasma cell dyscrasias [11]. In this report, we describe a patient with PNH associated with T cell LGL oligoclonal expansion and IgG l monoclonal gammopathy of undetermined significance (MGUS).…”
Section: Introductionmentioning
confidence: 87%
“…CD55 and CD59 deficiency has been studied in other diseases and correlated with its severity. [29][30][31][32][33][34][35][36] Yamaguchi et al 37 showed that 28.6% of the patients with aplastic anemia (AA) and 27.8% of the patients with myelodysplasia syndrome (MDS) presented a poor population of CD59 in erythrocytes. Wang et al 38 observed a significant CD55 and CD59 reduction in 52% of neutrophils in patients with AA not treated.…”
Section: C3 and C5 Convertasementioning
confidence: 99%